2016
DOI: 10.33844/mbr.2016.60281
|View full text |Cite
|
Sign up to set email alerts
|

The effect of real exchange rate on unemployment

Abstract: Unemployment is one of the problems that global economics, especially the economy of developing countries such as Iran is faced with. Therefore, there have been many studies to investigate the variables which affect unemployment in macroeconomics. Considering exchange rate volatility in recent years which have affected most of major variables of economy in Iran, this study tried to investigate the relationship between exchange rate and unemployment in Iran using the annual data of 30 years (from 1981 to 2012).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
3
12
1
Order By: Relevance
“…The Johansen cointegration test for the macro variables revealed that the variables are cointegrated which is in line with economic expectation that state that most macro-economic variables tends to exhibit long run relationship (Kwon and Shin, 1999). Since the variables are integrated of order one and also cointegrated, the FMOLS Bakhshi and Ebrahimi (2016) for Iran economy. The implication of our result shows that the Nigerian economy depends more on Importation.…”
Section: Data Analysis and Discussion Of Resultssupporting
confidence: 76%
“…The Johansen cointegration test for the macro variables revealed that the variables are cointegrated which is in line with economic expectation that state that most macro-economic variables tends to exhibit long run relationship (Kwon and Shin, 1999). Since the variables are integrated of order one and also cointegrated, the FMOLS Bakhshi and Ebrahimi (2016) for Iran economy. The implication of our result shows that the Nigerian economy depends more on Importation.…”
Section: Data Analysis and Discussion Of Resultssupporting
confidence: 76%
“…(2) A one SD impulse to UNEMP initially decreases lnEX up to 2 periods, and this response then sharply declines and hits the zero-line value in the period 2-3 from where it remains in the negative region during the period 3-12, albeit with an increasing tendency. This means that innovations to UNEMP will have asymmetric impacts on lnEX in the short as well as long-run and such findings validate the outcomes of (Arshad and Ali, 2016;Bakhshi and Ebrahimi, 2016). (3) A one SD innovation of INF to UNEMP initially hits the steady-state value in the 1 st period, and then sharply declines up to the 3 rd period and remains in the negative region up to the 8 th period where it again hits the steadystate level, and after that, it remains in the positive region but moves towards the zero line over periods.…”
Section: Results Of Impulse Responsessupporting
confidence: 78%
“…However, there are mixed findings exist about the correspondence between exchange rate-unemployment in the empirical macroeconomics literature. Some empirical studies have concluded that the connection between exchange rate vs. unemployment is inverse and these studies include (Chowdhury and Hossain, 2014;Kaur, 2014;Bakhshi and Ebrahimi, 2016); however, other empirical studies suggest that the relationship between the analyzed factors is positive, and this result has been confirmed from the findings of the study conducted by (Islam and Sajalal, 2019).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…An increase of RER by 10% increases unemployment by 5.5%, at a percent significance level and real exchange rate depreciation increases unemployment rate in ten Asian countries. This study has contrary outcome with Bakhshi and Ebrahimi (2016) where the relationship between real exchange rate and unemployment in Iran using the annual data of 30 years (from 1981 to 2012) demonstrated that there was a negative relationship between unemployment and exchange rate and economic growth had a significant and positive effect on unemployment. This finding agreed with Atya (2017) who estimated the effect of real exchange rate on unemployment in the Egyptian economy during the period 1985-2015 using three methods to estimation such ARDL, FMOLS and DOLS.…”
Section: Real Exchange Rate-unemployment Relationship Theorycontrasting
confidence: 76%